Carbon-conscious development: Examining FDI, economic growth, and CO2 emissions in Jordan - Alwaked, Ahmad A.; Al-qalawi, Usama Robin; Nawasreh, Ahmad (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the links between FDI, growth, and environmental impacts in Jordan. It evaluates short- and long-term links between FDI, growth, and carbon emissions. It also examines the EKC, PHVH, and PHLH for 1990-2022. The study uses the Autoregressive Distributed Lag (ARDL) model. It tests long-term relationships tied to these hypotheses. The ARDL bounds test found an inverse link between FDI and CO2 emissions. This supports the Pollution Halo Hypothesis. It also found a positive correlation between GDP and CO2 emissions. Yet, the results do not support the EKC hypothesis for Jordan. Causality testing shows a one-way link. CO2 emissions cause all other variables. FDI affects both GDP and its squared term. These insights stress the need for policies to boost FDI. This is vital in renewable energy, especially solar and wind. It will help Jordan’s sustainable development goals.